THE REGULATORY MECHANISMS OF THE UMBILICAL VEIN HEMODYNAMICS: CLINICAL CONCEPT - Lakhno, I. V.; Barannik, E. A.; Tkachov, A. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
It was performed the investigation of the umbilical vein blood flow Doppler spectrograms of 85 patients in the term 37–41 week of gestation and 22 persons of them had normal fetal condition. Intrauterine fetal growth restriction was diagnosed in 63 pregnant women. The spectral components of maximum blood flow velocity were defined. In case of physiological pregnancy umbilical vein blood flow was provided with proper myogenic contractile activity with the frequency of 7 Hz. It was also depended on the arterial component associated with fetal heart rate in the range of 2 Hz. It was determined that fetal compromise was associated with an increase of the slow-wave maternal origin processes with a frequency of 0,5 Hz in the umbilical venous hemodynamics regulation and depletion of the proper myogenic activity. The applied approach could improve current concepts of ergo-trophotropic mechanisms of fetal well-being.